Development of a time-resolved immunochromatographic strip for rapid and quantitative determination of deoxynivalenol - Wang, Jingneng; Wang, Lihua; Zhang, Hui; Mei, Xinglin; Qiu, Liangzhu; Liu, Jing; Zhou, Yongsong (Frontiers in Veterinary Science, 2023)
Deoxynivalenol (DON) contamination of food crops and feeds is almost impossible to avoid completely; however, through best management practices, this risk can be effectively managed and maximumly mitigated. Accurate and rapid detection of DON contamination as early in the entire value chain as possible is critical. To achieve this goal, we developed a DON test strip based on time-resolved fluorescence immunoassay (TRFIA) and a specific DON monoclonal antibody for the rapid quantification of DON in food crops and feeds. The strip displayed a good linearity (R2 = 0.9926), with a limit of quantification of 28.16 μg/kg, a wide linear range of 50 ~ 10000 μg/kg. The intra-batch coefficient of variation (CV) and the inter-batch CV was less than 5.00% and 6.60%, respectively. This TRFIA-DON test strip was applied to detect DON in real samples, and the accuracy and reliability were confirmed by liquid chromatography-mass spectrometry (LC-MS/MS). Results showed that the relative standard deviation between the DON strips and LC-MS/MS was less than 9%. The recovery rates in corn samples ranged from 92% to 104%. The established TRFIA-DON test strip had the characteristics of high sensitivity, high accuracy, and a wide linear range which was suitable for rapid and quantitative determination of DON in food crops and feeds at both on-site and laboratory.